Agricultural technology adoption in the Feed the Future zone of influence in Bangladesh - Ahmed, Akhter; Hernandez, Ricardo; Naher, Firdousi; Data Analysis and Technical Assistance Limited (International Food Policy Research Institute, 2014)
Upon request from the US Agency for International Development (USAID), the International Food Policy Research Institute’s Policy Research and Strategy Support Program in Bangladesh (IFPRI-PRSSP) developed and began a study on the adoption of agricultural technologies in USAID’s Feed the Future (FTF) zone of influence in the south and southwest regions of the country. FTF is the US government’s global hunger and food security initiative to support country-driven approaches to address the root causes of poverty, hunger, and undernutrition. In Bangladesh, FTF’s collective efforts aim to improve the livelihood and nutritional status of households through: (1) increased on-farm productivity, (2) increased investment in market systems and value chains, (3) enhanced food security policy and planning capacity, (4) enhanced agriculture innovation capacity, and (5) improved nutritional status of rural poor. The agricultural technologies evaluated in this study are: (1) Urea deep placement (UDP)-popularly known as “Guti urea”; and (2) Modern, stress-tolerant varieties of rice.